Sequential and tank-mix application of herbicides for weed management ensuring higher productivity of soybean (Glycine max) - SHARMA, RAJVIR; S, RENJITH P (The Indian Journal of Agricultural Sciences, 2016)
A field experiment aimed to evaluate the bioefficacy of pre- and post-emergence herbicides on weed dynamics and yield in soybean (Glycine max L.) was conducted during kharif season of 2011 and 2012 at New Delhi. Herbicide treatments provided weed control efficiency ranging from 43.25% to 72.81% over weedy check. Sequential application of metribuzin @ 250 g/ha as pre-emergence followed by (fb) propaquizafop @ 50 g/ha at 3 weeks after sowing (WAS) as post-emergence was found most effective in reducing weed growth, augmenting seed and stover yield with the highest net monetary return. Combined application of pendimethalin @ 750 g/ha as pre-emergence fb propaquizafop @ 50 g/ha at 3 WAS was also equally effective. Quantitative analysis of soil microflora showed that herbicidal application significantly suppressed the microbial population at 30 DAS which recovered at the harvest of soybean.